A Comparison of Shear Bond Strength Values of Recycled Self-Ligating Ceramic Brackets with a New Ones (An-in Vitro Study) - Zain Alabideen Ahmed; Mustafa M. Al-Khatieeb (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: The aim of the current study was to assess the effects of different recyclrd procedures on shearbond strength and morphological characteristics of deboned mechanically retaining self-ligating ceramicbrackets’ bases, then compare the results with the new brackets of the same company.Material and Methods: Forty-eight mechanical retentive self-ligating ceramic brackets from Damon®ClearTM company were used, thirty-six of these brackets were bonded to non-etched and slightly dampbuccal tooth surface in order to permit an easy debonding of these brackets by dental tweezer, these debondedbrackets were then allocated into three experimental groups (12 per group): recycled by sandblasting,recycled via an Er, Cr: YSGG laser irradiation, and recycled by flame. After recycled, twelve new brackets(the control) plus the previously thirty six reconditioned brackets were bonded to the forty-eight premolarteeth following standardized bonding procedure.Results: There were highly significant differences in the mean shear bond strength values among all groupsusing analysis of variance F-test; in addition, the mean shear bond strength of new brackets had the highestmean value of 22.90 Mpa, followed by Er,Cr:YSGG laser group 20.29 Mpa, then sandblasted group of 11.42Mpa, while flame group had the lowest mean shear bond strength value of 7.63 Mpa; furthermore, the resultsshowed a significant difference in adhesive remnant index (ARI) among all groups.Conclusion: all recyclrd procedures would result in a clinically acceptable shear bond strength value. TheEr,Cr:YSGG recyclrd procedure can effectively eradicate the adhesive from the bases of ceramic bracketswithout jeopardizing them; thus, this technique can be preferred over other recyclrd procedures.